1996
DOI: 10.1017/s0890060400001645
|View full text |Cite
|
Sign up to set email alerts
|

An approach to functional synthesis of mechanical design Concepts: Theory, applications, and emerging research issues

Abstract: Conceptual design is an early stage in the design process that involves the generation of solution concepts to satisfy the functional requirements of a design problem. Usually, there are many solutions to a design problem; therefore, there is scope for producing improved designs if one could explore a solution space larger than is presently possible. An approach would be to use the computer to synthesize a wide variety of concepts for a given problem, and allow designers to explore these before developing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 16 publications
0
53
0
Order By: Relevance
“…This research extends earlier research on a functional synthesis approach that produces a wide variety of abstract concepts to mechanical design problems, which involve transmission and conversion of mechanical forces and motions [15]. For a given design problem, this approach can produce an exhaustive set of concepts in terms of their spatial configurations.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…This research extends earlier research on a functional synthesis approach that produces a wide variety of abstract concepts to mechanical design problems, which involve transmission and conversion of mechanical forces and motions [15]. For a given design problem, this approach can produce an exhaustive set of concepts in terms of their spatial configurations.…”
Section: Introductionmentioning
confidence: 57%
“…These are then offered to designers for exploration. This approach has been tested by means of case studies and hands-on experiments involving experienced designers [15]. It was found that the number and variety of solutions generated by using this approach were always larger than those of the designers.…”
Section: Introductionmentioning
confidence: 99%
“…The variety of functional reasoning approaches (see [111, 112, e.g.] for a summary), the areas within which they are explored (e.g., in product or system architecture by Stone [44], in biologically inspired design [105,113,114,115], in computational synthesis [116,117,118,119,120,121], in design by analogy and analogical reasoning [122,123,96,124,125], and in efficient sharing and search [126,127,128]) are testimony to the prolific research in the area of function. A summary of functional representation approaches can be found in two special issues of AIEDAM [129,130,131], and a summary of major approaches within the other two tasks can be found in [111,132,112].…”
Section: Trends In the Evolution Of Research Into Functionalmentioning
confidence: 99%
“…Design synthesis of engineering artifacts has been a significant research area, especially in the fields of structures [4,24,25,9], mechanical systems [26,16,8,6,7], MEMS and VLSI -a good summary of which is available in [1]. Techniques ranging from search algorithms, stochastic and gradient based optimization, evolutionary and genetic algorithms, have been used in combination with discrete and continuum approaches, bond graph methods, graph grammars, design rules and more for the purpose of synthesis of these systems.…”
Section: Introductionmentioning
confidence: 99%